MICROSOFT SWAY APPLICATION TO ENHANCE STUDENTS’ READING ABILITY OF DESCRIPTIVE TEXT - Yolanda Rizki Amalia; Hermansyah Hermansyah; Santi Mayasari (Esteem Journal of English Education Study Programme, 2023)
The research aimed to determine if there was a significant difference in the reading achievement of students who were taught using Microsoft Sway compared to those who were not. A quantitative method with a quasiexperimental design was employed for the study. Data collection involved a pre-test and post-test, while descriptive statistics were used for data analysis. The results showed that the independent sample t-test gave a value of 3.226, which was higher than the t-critical value of 2.000 at a 95% significance level with 65 degrees of freedom. This indicates that the obtained t-value exceeded the expected value from the t-table (t-obtained 3.226 > t-table 2.000). As a result, the null hypothesis was rejected and the alternative hypothesis was accepted.